Strength training protocols in hemiparetic individuals post stroke: a systematic review - Diogo Dutra Barbosa; Mirele Ruff Trojahn; Daniela Veber Gularte Porto; Guilherme Scotta Hentschke; Vítor Scotta Hentschke (Editora Champagnat, 2018)
Abstract Introduction: Hemiparesis is one of the main sequels of stroke. Evidence suggests that muscle strength exercises are important in rehabilitation programs for hemiparetic patients, but wide variation in previously studied protocols makes the most suitable choice difficult in clinical practice. Objective: The aim of this study was to investigate strength training protocols for people with hemiparesis after stroke. Methods: A systematic review of literature was performed in the PubMed, PEDro (Physiotherapy Evidence Database), SciELO (Scientific Electronic Library Online), and LILACS (Latin American and Caribbean Literature in Health Science) databases. Only controlled clinical studies that contained strength training protocols for hemiparesis after stroke were selected. Results: In total, 562 articles were found. Of them, 12 were accepted for the systematic review. Although strength training protocols are effective in hemiparetic patients, we did not found a standard method for strength training. Conclusion: This systematic revision highlights the lack of a standard protocol for strength training, considering the following training parameters: volume, intensity, frequency, series, and repetitions. Isotonic exercises are most commonly used.